DIGITAL RIGHTS REGULATION IN THE AI ERA: PRIVACY PROTECTION AND CONSUMER RIGHTS IN INDONESIA - Endang Fatmawati; Adlhan Nury M. A. S. A.; Minan Faiz Fausta Rafa; Ananda Rivaldo Sari; Masnilam Hasibuan (Ikatan Dosen Menulis, 2025)
This study examines the regulation of digital rights in the era of artificial intelligence, with a specific focus on privacy protection and consumer rights in Indonesia. Rapid diffusion of AI-driven services has intensified data processing practices, algorithmic decision-making, and cross-sector digital consumption, raising complex legal and ethical concerns. Using a structured literature review methodology, the study synthesizes peer-reviewed articles, policy documents, and authoritative legal sources to map prevailing regulatory approaches and debates. The review analyzes international frameworks on data protection and consumer protection to identify normative standards relevant to AI governance. Findings indicate that AI systems amplify risks related to personal data misuse, opacity, and power asymmetries between platforms and consumers. In the Indonesian context, existing digital regulations provide a foundational basis for rights protection but reveal gaps in enforcement capacity, interoperability, and AI-specific safeguards. The literature further highlights tensions between innovation-driven policy agendas and the need for robust accountability and transparency mechanisms. This study contributes by integrating privacy and consumer protection perspectives within a unified digital rights framework tailored to AI applications. Policy implications underscore the importance of adaptive regulation, institutional coordination, and rights-based oversight to address AI-related harms. The article concludes by outlining directions for future research on AI governance and digital rights reform in emerging economies.